Perception of risks and safe handling practices of corpses among morticians in Ibadan, Oyo state - Akinyemi, Oluwasun Oladapo; Adenaike, Esther M.; Ilesanmi, Olayinka S.; Ojezele, Samuel O. (International Journal Of Community Medicine And Public Health, 2021)
Background: It is well known in many Sub-Saharan countries that many morgues that are designed and built to earlier standard are no longer compatible with current occupational health and safety practices. This study therefore aimed to investigate the perception of risks involved and safe handling of corpses among morticians in Ibadan, Oyo State, Nigeria. Methods: We conducted a cross-sectional study among 42 morticians in Ibadan in 2017 using both quantitative and qualitative methods of data collection. An interviewer-administered questionnaire was used to obtain information from morticians. A key informant interview was also conducted with each supervisor of the various facilities. Results: Respondents’ mean age was 42.1±11.4 years, 39 (95.1%) were males, and 14 (35%) had no formal education. The most dangerous communicable diseases that the respondents were aware of included Lassa fever among 38 (95.0%), Ebola among 35 (87.5%), tetanus among 34 (85.0%), tuberculosis among 31 (77.5%), and hepatitis B among 25 (62.5%). In all, 36 (90%) of the respondents had inhaled chemicals during work leading to cough, excessive sneezing and eye irritation. Protective gown was well known among all 42 (100%) respondents. Work-associated injuries such as sharp injury, splash of chemicals, slip, trip and falls were least ranked. Some of the facilities (33%) had written program based on the requirement of the World Health Organization. Conclusions: Government, stakeholders and bodies responsible for managing mortuaries should not only pass law and enforce them but also provide avenues (seminars, lectures, webinars etc.) where knowledge can be shared and modern industry safe practices can be achieved.